2022
DOI: 10.3390/biomedicines10030525
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Early Peripheral Immune Responses in Patients with Sepsis and Septic Shock

Abstract: (1) Background: Sepsis is a life-threatening condition caused by an abnormal host response to infection that produces altered physiological responses causing tissue damage and can result in organ dysfunction and, in some cases, death. Although sepsis is characterized by a malfunction of the immune system leading to an altered immune response and immunosuppression, the high complexity of the pathophysiology of sepsis requires further investigation to characterize the immune response in sepsis and septic shock. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 75 publications
(82 reference statements)
4
9
0
Order By: Relevance
“…Extracellular histones are responsible for cell damage via several transduction pathways [ 15 , 20 , 28 31 ]. It has been demonstrated that circulating histones mediate innate immunity dysregulation, triggering inflammatory responses, endothelium injury, and coagulation [ 28 , 32 38 ], thus their levels are associated with sepsis severity, tissue damage and risk of death [ 17 , 17 , 21 , 21 23 , 39 , 40 ]. This last mortal event is influenced mainly by endothelium damage and vascular endothelial cell death, which may in turn induce barrier function impairment, decreased blood flow, vascular tone and blood pressure, and activation of the coagulation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular histones are responsible for cell damage via several transduction pathways [ 15 , 20 , 28 31 ]. It has been demonstrated that circulating histones mediate innate immunity dysregulation, triggering inflammatory responses, endothelium injury, and coagulation [ 28 , 32 38 ], thus their levels are associated with sepsis severity, tissue damage and risk of death [ 17 , 17 , 21 , 21 23 , 39 , 40 ]. This last mortal event is influenced mainly by endothelium damage and vascular endothelial cell death, which may in turn induce barrier function impairment, decreased blood flow, vascular tone and blood pressure, and activation of the coagulation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Gogos et al, recently found differences between the early status of the innate and adaptive immune system between sepsis and SS patients, and those differences were related to the infection source [ 59 ]. Regarding innate and adaptive immune activation, our group also showed that during the first stages of sepsis, adaptive immunity is not completely active [ 60 ]. In line with these observations, we propose that, during the first stages of sepsis, innate immunity is overexpressed in comparison with the later stages of sepsis, especially in the SS patient group.…”
Section: Discussionmentioning
confidence: 99%
“…The exacerbated hyper-inflammatory response can also damage non-infected tissues and lead to dysfunction of different organs and systems linked to hypotension, vasculature damage, and coagulation events, aggravating the disease status of septic patients, and producing early deaths at the initial stages of sepsis ( 2 ). The hyperinflammatory process is an acute event occurring usually at initial stages of sepsis just after infection ( 3 5 ). A compensatory anti-inflammatory response syndrome (CARS) can sometimes simultaneously occur, which can induce long-term immunosuppression, leading to secondary infections and most sepsis-associated late deaths ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Myeloid-derived suppressor cells (MDSCs) are also involved in sepsis-induced immunosuppression throughout the production of arginase 1 and contribute to T-cell dysfunction ( 16 ). Importantly, levels of MDSCs mediators and the expression of genes with immunosuppressive functions, such as S100A8/A9 , S100A12 , and ARG1 , are highly elevated in patients with sepsis ( 3 , 16 ). Despite accumulating scientific evidence on the pathogenetic mechanisms underlying sepsis, data explaining sepsis-induced immunosuppression is still lacking, and the molecular mechanisms occurring in the host leading to immunosuppression in human sepsis remain poorly understood ( 6 , 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%